CLINICAL MORPHOLOGY OF LIVER: CHOLESTASES - Tsyrkunov V. M.; Prokopchik N. I.; Andreev V. P. (Žurnal Grodnenskogo Gosudarstvennogo Medicinskogo Universiteta, 2018)
Background. Cholestasis, together with necrosis, apoptosis and fibrosis, is the main pathological syndrome in chronic diffuse lesions of the liver of various etiologies. In the literature on intrahepatic cholestasis (HPH), there are not enough materials that demonstrate the morphological signs of HPH. The aim of the study is to present the morphological characteristics of the localization of lesions in the liver with different types of HPH. Material and methods. A complex method of morphological diagnostics based on a biopsy specimen study in the same patient was used to diagnose HPH using several methods simultaneously: classical light microscopy supplemented with original techniques for visualization of ultrathin sections and electron microscopy. Results. Morphological variants of HPH depending on localization of lesions are presented in the article: intralobular cholestasis (hepatocellular and canalicular) and extralobular cholestasis. The illustrations in the article clearly demonstrate the features of morphological changes in the liver in viral, alcoholic, medicinal, metabolic, genetic lesions of the liver, accompanied by a syndrome of HPH. The available variants of HPH are divided taking into account the three main reasons for the formation of HPH: violation of the mechanisms of bile formation, disruption of mechanisms of bile transport at the level of hepatocytes and damage to intrahepatic bile ducts. As a differential diagnosis, an example of subhepatic cholestasis is given. Conclusions. The variety of reasons for the development of HPH, the complexity of topical diagnosis and differential diagnosis of various options, the relatively low effectiveness of conservative therapy, and the high probability of surgical intervention to exclude surgical pathology make this problem one of the most important in therapeutic and infectious hepatology. The use of the complex method of morphological diagnostics makes it possible to more accurately visualize the initial stages of HPH, to assume its origin and to apply preventive therapy taking into account the pathogenetic mechanisms of development and its morphological characteristics.